ответ: -0,1. 1,5.
Пошаговое объяснение:
(6x-9)(4x+0,4)=0;
24x²+2.4x-36x-3.6 = 0;
24x²-33.6-3.6=0;
a=24; b=-33.6; c=-3.6;
D=b²-4ac=(-33.6)²-4*24*(-3.6) = 1 128,96 + 345,6 = 1 474,56>0 - 2 корня
x1,2 = (-b±√D)/2a = (-(-33.6)±√1474.56)/2*24= (33.6±38.4)/48;
x1=(33.6+38.4)/48 = 1.5;
x2 = (33.6-38.4)/48 = -0.1.
ответ: -0,1. 1,5.
Пошаговое объяснение:
(6x-9)(4x+0,4)=0;
24x²+2.4x-36x-3.6 = 0;
24x²-33.6-3.6=0;
a=24; b=-33.6; c=-3.6;
D=b²-4ac=(-33.6)²-4*24*(-3.6) = 1 128,96 + 345,6 = 1 474,56>0 - 2 корня
x1,2 = (-b±√D)/2a = (-(-33.6)±√1474.56)/2*24= (33.6±38.4)/48;
x1=(33.6+38.4)/48 = 1.5;
x2 = (33.6-38.4)/48 = -0.1.